A Band‐Edge Potential Gradient Heterostructure to Enhance Electron Extraction Efficiency of the Electron Transport Layer in High‐Performance Perovskite Solar Cells. (15th May 2017) - Hou, Yu; Chen, Xiao; Yang, Shuang; Li, Chunzhong; Zhao, Huijun; Yang, Hua Gui
Abstract : As the key component in efficient perovskite solar cells, the electron transport layer (ETL) can selectively collect photogenerated charge carriers produced in perovskite absorbers and prevent the recombination of carriers at interfaces, thus ensuring a high power conversion efficiency. Compared with the conventional single‐ or dual‐layered ETLs, a gradient heterojunction (GHJ) strategy is more attractive to facilitate charge separation because the potential gradient created at an appropriately structured heterojunction can act as a driving force to regulate the electron transport toward a desired direction. Here, a SnO2 /TiO2 GHJ interlayer configuration inside the ETL is reported to simultaneously achieve effective extraction and efficient transport of photoelectrons. With such an interlayer configuration, the GHJs formed at the perovskite/ETL interface act collectively to extract photogenerated electrons from the perovskite layer, while GHJs formed at the boundaries of the interconnected SnO2 and TiO2 networks throughout the entire ETL layer can extract electron from the slow electron mobility TiO2 network to the high electron mobility SnO2 network. Devices based on GHJ ETL exhibit a champion power conversion efficiency of 18.08%, which is significantly higher than that obtained from the compact TiO2 ETL constructed under the comparable conditions. Abstract : A gradient heterojunction electron transport layer (GHJ ETL), prepared by a facile low‐temperature route, is utilized in perovskite solar cells (PSCs) for the first time. PSCs based on the potential GHJ ETL demonstrate an efficiency of 18.08% with less hysteresis effect, which is due to excellent management of charge transport and recombination.